Wild halophytic species as forage sources: key aspects for plant breeding - Marinoni, Lorena del Rosario; Zabala, Juan Marcelo; Taleisnik, Edith; Schrauf, Gustavo Enrique; Richard, Geraldina Alicia; Tomas, Pablo Andrés; Giavedoni, Julio Alberto; Pensiero, José Francisco (Wiley; British Grassland Society; European Grassland Federation, 2019)
The use of wild halophytic species as forage resources in saline environments has gained increasing attention. Argentina ranks third in area of saline soils in the world, with a third of its territory showing various degrees of salinity, sodicity and/or alkalinity. On this type of soils, rangelands are the main forage resource for livestock production. Many wild species have forage potential and can also be used for the rehabilitation of rangelands and for intercropping. Information about these species, as well as on the physiological and genetic bases associated with salinity tolerance, provides relevant tools for efficient selection methods. This study addresses Argentine wild halophyte species with forage potential and describes selection criteria with an emphasis on the following taxa: (a) Poaceae: subfamily Chloridoideae and tribes Paniceae and Triticeae, (b) Fabaceae and (c) Amaranthaceae (formerly known as Chenopodiaceae). The review is intended to contribute to the general discussion on strategies for the improvement of wild plant genetic resources, using forage species naturally growing in saline soils in Argentina as a case study.